2016
DOI: 10.1063/1.4967841
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of TbAs films

Abstract: We report on the molecular beam epitaxy growth and characterization of TbAs films. In situ reflection high energy electron diffraction and ex situ high resolution X-ray diffraction, reciprocal space mapping, and both scanning and transmission electron microscopy are used to confirm the complete film growth and study the films' morphology. Spectrophotometry measurements provide the energy of optical transitions, revealing a red shift in optical band gap with increasing thickness. The Hall effect measurements sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Double-side polished intrinsic silicon wafers were used as substrates for the PEDOT:PSS conductivity measurements. Conductivity measurements were carried out by the van der Pauw technique on a custom built room temperature resistivity and Hall Effect system [11]. The resistivity of the films was measured twice (bi-directional by switching the four contacts between voltage and current probes) and the resulting values were averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Double-side polished intrinsic silicon wafers were used as substrates for the PEDOT:PSS conductivity measurements. Conductivity measurements were carried out by the van der Pauw technique on a custom built room temperature resistivity and Hall Effect system [11]. The resistivity of the films was measured twice (bi-directional by switching the four contacts between voltage and current probes) and the resulting values were averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the compatibility with conventional III-V semiconductors, we expect that the later can serve as substrates for epitaxial growth of RE-V, as demonstrated in the case of (In)GaAs/ErAs 5,8,9 and GaSb/LuSb. 6 In this context, it is important to know the workfunction of these materials to understand the formation of Schottky barriers and any possible charge transfer across the III-V/RE-V interfaces.…”
Section: Carrier Concentrations In Re-vmentioning
confidence: 99%
“…This approach has allowed us to distinguish the underlying mechanism behind the observed magnetoresistance behavior while establishing the efficacy of few atomic layer geometries in controlling electronic properties, which can be readily extended to other semimetallic systems. Although the presence of surface states at the interface between a rock salt and a zinc blende crystal structure ( 34 36 ) had been speculated in earlier studies, our experimental and theoretical work established the presence of a 2D hole gas at this technologically relevant heterointerface ( 37 ) and also elucidated its origin, which significantly affects the electronic and transport properties in the ultrathin limit. We have shown that controlling the nature of chemical bonding at the interface offers a novel route to realize 2D hole gas, which is distinct from a traditional 2D hole gas that arises because of the formation of accumulation layer near the interface as a result of band bending in semiconductors.…”
Section: Resultsmentioning
confidence: 62%